Trust and truth - Tore Ellingsen; Magnus Johannesson; Jannie Lilja; Henrik Zetterqvist (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
In a laboratory experiment, we create relationships between pairs of anonymous subjects through a Prisoners' dilemma game. Thereafter the same subjects play a private values (sealed-bid double auction) bargaining game with or without communication. Communication substantially increases bargaining efficiency among subjects who cooperated in the Prisoners' dilemma, but has no significant effect on bargaining outcomes when one subject defected. Subjects who cooperated in the Prisoners' dilemma bid more aggresively if their opponent defected. Cooperators also lie more about their valuations when their opponent defected: Compared to the case of mutual cooperation, the cooperators' rate of honest revelation decreases from 64% to 6% and the rate of outright deception increases from 7% to 53%. Our results provide qualitatively new evidence that many people are strong recipricators: They are willing to bear private costs in order to reward good behavior and punish bad behavior, even when the rewards and punishments are unobservable.
Keywords: C91; D74; Z13; 330; Bargaining; Communication; Honesty; Trust; Strong reciprocity; Soziales Verhalten; Emotion; Kommunikation; Gefangenendilemma; Verhandlungstheorie; Test